The effects of computerised decision support systems on nursing and allied health professional performance and patient outcomes: a systematic review and user contextualisation - Carl Thompson; Teumzghi Mebrahtu; Sarah Skyrme; Karen Bloor; Deidre Andre; Anne Maree Keenan; Alison Ledward; Huiqin Yang; Rebecca Randell (Health and Social Care Delivery Research)
Background Computerised decision support systems (CDSS) are widely used by nurses and allied health professionals but their effect on clinical performance and patient outcomes is uncertain. Objectives Evaluate the effects of clinical decision support systems use on nurses’, midwives’ and allied health professionals’ performance and patient outcomes and sense-check the results with developers and users. Eligibility criteria Comparative studies (randomised controlled trials (RCTs), non-randomised trials, controlled before-and-after (CBA) studies, interrupted time series (ITS) and repeated measures studies comparing) of CDSS versus usual care from nurses, midwives or other allied health professionals. Information sources Nineteen bibliographic databases searched October 2019 and February 2021. Risk of bias Assessed using structured risk of bias guidelines; almost all included studies were at high risk of bias. Synthesis of results Heterogeneity between interventions and outcomes necessitated narrative synthesis and grouping by: similarity in focus or CDSS-type, targeted health professionals, patient group, outcomes reported and study design. Included studies Of 36,106 initial records, 262 studies were assessed for eligibility, with 35 included: 28 RCTs (80%), 3 CBA studies (8.6%), 3 ITS (8.6%) and 1 non-randomised trial, a total of 1318 health professionals and 67,595 patient participants. Few studies were multi-site and most focused on decision-making by nurses (71%) or paramedics (5.7%). Standalone, computer-based CDSS featured in 88.7% of the studies; only 8.6% of the studies involved ‘smart’ mobile or handheld technology. Care processes – including adherence to guidance – were positively influenced in 47% of the measures adopted. For example, nurses’ adherence to hand disinfection guidance, insulin dosing, on-time blood sampling, and documenting care were improved if they used CDSS. Patient care outcomes were statistically – if not always clinically – significantly improved in 40.7% of indicators. For example, lower numbers of falls and pressure ulcers, better glycaemic control, screening of malnutrition and obesity, and accurate triaging were features of professionals using CDSS compared to those who were not. Evidence limitations Allied health professionals (AHPs) were underrepresented compared to nurses; systems, studies and outcomes were heterogeneous, preventing statistical aggregation; very wide confidence intervals around effects meant clinical significance was questionable; decision and implementation theory that would have helped interpret effects – including null effects – was largely absent; economic data were scant and diverse, preventing estimation of overall cost-effectiveness. Interpretation CDSS can positively influence selected aspects of nurses’, midwives’ and AHPs’ performance and care outcomes. Comparative research is generally of low quality and outcomes wide ranging and heterogeneous. After more than a decade of synthesised research into CDSS in healthcare professions other than medicine, the effect on processes and outcomes remains uncertain. Higher-quality, theoretically informed, evaluative research that addresses the economics of CDSS development and implementation is still required. Future work Developing nursing CDSS and primary research evaluation. Funding This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in Health and Social Care Delivery Research; 2023. See the NIHR Journals Library website for further project information. Registration PROSPERO 1 [number: CRD42019147773]. Plain language summary Computerised decision support systems (CDSS) are software or computer-based technologies providing advice to professionals making clinical decisions – for example, which patients to treat first in emergency departments. CDSS improve some doctors’ decisions and patients’ outcomes, but we don’t know if they improve nurses’, midwives’ and therapists’ or other staff decisions and patient outcomes. Research into, and health professionals’ use of, technology – for example, in video consultations – has grown since the last relevant systematic review in 2009. We systematically searched electronic databases for research measuring how well nurses, midwifes and other therapists/staff followed CDSS advice, how CDSS influence their decisions, how safe CDSS are, and their financial costs and benefits. We interviewed CDSS users and developers and some patient representatives from a general practice to help understand our findings. Of 35 relevant studies – from 36,106 initially found – most (71%) focused on nurses. Just over half (57%) involved hospital-based staff, and three-quarters (75%) were from richer countries like the USA or the UK. Research quality had not noticeably improved since 2009 and all studies were at risk of potentially misleading readers. CDSS improved care in just under half (47%) of professional behaviours, such as following hand-disinfection guidance, working out insulin doses, and sampling blood on time. Patient care – judged using outcomes like falls, pressure ulcers, diabetes control and triage accuracy – was better in 41% of the care measured. There wasn’t enough evidence to judge CDSS safety or the financial costs and benefits of systems. CDSS can improve some nursing and therapist decisions and some patient outcomes. Studies mostly measure different behaviours and outcomes, making comparing them hard. Theories explaining or predicting how decision support systems might work are not used enough when designing, implementing or evaluating CDSS. More research into the financial costs and benefits of CDSS and higher-quality evidence of their effects are still needed. Whether decision support for nurses, midwives and other therapists reliably improves decision-making remains uncertain.